Study on Customer Experience Affecting Human Kansei - Nagasawa, Shin’ya (Modern Perspectives in Economics, Business and Management Vol. 6, 2021)
The purpose of this paper is to examine the relationships and meaning of the customer experience approach, which involves manufacturing and fabrication influenced by kansei. This paper attempts to respond to the question, what are the products that appeal to the senses? and to examine kansei marketing, customer experience and kansei marketing, customer experience and Strategic Experiential Modules, customer experience and kansei quality, relationships between the information processing of the senses and customer experience, relationships between functional benefits and customer experience, and summaries of the examples, the manufacturer’s product development capabilities constitute a source of the customers’ experience, creating the customer experience of products, including lifestyle and culture.